IMPLEMENTASI PENGUKURAN PRODUKTIVITAS DENGAN METODE MARVIN E. MUNDEL DI UKM ROTI BERNAS - Oscar Nemesis (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
Bread Bernas SME is a home industry that is engaged in producing bread. The problems that exist in Bread Bernas SME are the amount of bread production that cannot meet production targets and production costs such as raw material costs have increased but the amount of production output has decreased. This study aims to determine the productivity index, influencing factors, and proposed improvements to increase productivity. This productivity measurement uses the Marvin E. Mundel method by calculating the partial and total productivity indices. The results of the productivity index for each input (depreciation, labor, materials, electrical energy, and maintenance) in 2020 as a period measured successively are 80.76%; 84.40%; 87.76%; 102.10%; 68.30%; and a total index of 87.02%. To increase productivity, it can be implemented such as adding radios and speakers, adding fans, implementing a floor cleaning schedule and production machines, and so on. Implementation is carried out in April and May 2021. The results of the productivity index after implementation of each input (depreciation, labor, materials, electrical energy, and maintenance) in April 2021 respectively are 103.17%; 106.48%; 113.45%; 112.04%; 107.89% and a total index of 112.06%. Meanwhile, the productivity index in May 2021 was 106.07% in a row; 107.36%; 111.74%; 110.20%; 102.43%; and the total index is 109.55%.